Differences in Accounting Laboratory Learning Outcomes Based on Educational Background - Saripah (PT. Maju Malaqbi Makkarana, 2024)
This research aims to find out how student learning outcomes differ in the Accounting Laboratory course based on previous educational background. The population in this sample is all 91 students who filled out the Googleform provided. The sample size was obtained using the Yamane formula for the two independent variables, namely SMK with 40 students and SMA with 20 students. The type of research in this research is quantitative comparative using the independent sample t-test analysis technique, with the test carried out being a difference test of one group of samples (pairs). The results of this research are that there is no statistically significant difference between the learning outcomes of students with vocational/MAK backgrounds and the learning outcomes of students with high school/MA backgrounds. Keywords: Learning Outcomes, Educational Background